The Middle Passage in Black Expressive Culture - Mózes, Dorottya (Hungarian Journal of English and American Studies, 2020)
Book review:Wilker, Frank. Cultural Memories of Origin: Trauma, Memory, and Imagery in African American Narratives of the Middle Passage. Heidelberg: Universitätsverlag Winter, 2017. 302 pages. ISBN 9783825361921. Hb. $49.05.